MULTIDISCIPLINARITY, TRANSLATIONAL RESEARCH AND COMMUNITY-ENGAGEMENT: AN APPROACH TO ADDRESS SOCIOECONOMIC AILS AMONGST DAY LABOURERS IN POTCHEFSTROOM, SOUTH AFRICA - de Wet, Christa (European Scientific Journal, ESJ, 2015)
“No political democracy can survive and flourish if the mass of our people remain in poverty, without land, without tangible prospects for a better life. Attacking poverty and deprivation must therefore be the first priority of a democratic government.” (RSA, 1994, para. 1.2.9). For many years global leaders trusted that the socio-economic phenomena of poverty and inequality would resolve itself in the midst of growth and development. Regrettably, it has not! Poverty and inequality proved to be two of the most persistent global challenges that continue to infiltrate international discourse. The undeniable truth of these challenges is the global impasse of 1.2 billion people that remain in a relentlessly inflicted state of poverty and inequality. The Republic of South Africa, as young democratic developmental state is not left unaffected by these phenomena. South Africa’s Reconstruction and Development Programme (RDP), (RSA, 1994), eloquently described the fact that “[O]ur history has been a bitter one dominated by colonialism, racism, apartheid, sexism and repressive labour policies. The result is that poverty and degradation exist side by side with modern cities and a developed mining, industrial and commercial infrastructure. Our income distribution is racially distorted and ranks as one of the most unequal in the world – lavish wealth and abject poverty characterise our society.” (para. 1.2.1). Acting from the understanding of such a sombre reality, traces of corrective measures are visible in every strategic driver and programme, designed and introduced by the South African Government. But, despite diligent efforts, these challenges remain. A critical question that lingers is: could it be that extant societal systems and cultural associations literally add further fuel to a blazing fire? Deep in the heartland of South Africa lays a city known as Potchefstroom. This City is home to a public university, recognised as the North-West University, Potchefstroom Campus. Two of the disciplines in the Social Sciences at the North-West University, Potchefstroom Campus, Public Management and Governance and Social Anthropology, engaged in a multidisciplinary intervention to unravel the deep-rooted character of poverty and inequality to establish a micro solution to these ails, particularly in the lives of day labourers. A multidisciplinary approach and translational research, implemented amongst the students of these two disciplines, offered an opportunity to obtain two richly theoretical and praxis infused angles of incidence on the phenomena of poverty and inequality. In addition, the students from Public Management and Governance participated in community-engagement, which served as a preparative grounding to critical and analytical thinking and complex problem solving skills, prior to their entry into the South African Public Service. Students in Public Management and Governance were not only educated in the levels of complexity infused by poverty and inequality as socio-economic phenomena, but were also in a position to seek sustainable solutions to address these ails through the application of Programme and Project Management theory, principles and tools as part of their academic curriculum. This article investigates the contribution that a multidisciplinary approach, translational research and community-engagement can instil into an extant academic curriculum of students in order to discover real-life solutions to socio-economic phenomena.